Biomass composition and ash melting behaviour of selected miscanthus genotypes in Southern Germany. (15th September 2016) - Iqbal, Y.; Lewandowski, I.
Highlights: Contents of ash, K and Cl are good indicators of biomass combustion quality. Optimization of biomass composition through crop management strategies can be a good tool to improve the ash melting behaviour. Sintering tendencies were lower for the thin stemmed M. sinensis genotypes than for all other genotypes. Abstract: Optimization of biomass composition can lead to reduction of both ash-related problems such as slagging, fouling and corrosion as well as emissions (NO x, SO x ) when combusted. This study aims to monitor the ash melting behaviour of biomass over a period of eight years from 15 miscanthus genotypes grown at Ihinger Hof research station, near Stuttgart, Germany and explain the relationship between biomass composition and ash melting behaviour. To do this, biomass ash samples were prepared and subjected to different heating treatments (800–1100 °C) and categorized into 4 ash-fusion classes based on microscopic observations. The outcome of the study reveals that the sintering tendencies were lower for the Miscanthus sinensis genotypes than for all other genotypes but these genotypes are low yielding. Furthermore, M. sinensis hybrids and Miscanthus sacchariflorus performed better than Miscanthus  ×  giganteus genotypes at higher temperatures. The correlation analysis between biomass composition and ash melting behaviour suggests that ash, K and Cl contents play a key role in inducing ash-related problems.